2015
DOI: 10.1016/j.socscimed.2014.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Taking pills for developmental ails in Southern Brazil: The biologization of adolescence?

Abstract: In the late 1990s researchers in Pelotas Southern Brazil began documenting what they considered to be unacceptably high rates of licensed psychotropic use among individuals of all ages, including youth. This came as a surprise, since the vast majority of psychiatrists in Pelotas draw on psychoanalytic theory and approach pharmaceutical use, especially for children and adolescents, in a consciously tempered way. Drawing from a longitudinal ethnographic sub-study, part of a larger 1982 birth cohort study, this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Yet their overwhelming sense of disempowerment often prompted a return to suspicious hermeneutics centred on resisting epistemic reductionism. While engendering a sense of agency, this also fed what I have described elsewhere as a recursive gridlock of biopolitical 'reproduction' and bio-epistemic 'resistance' (Béhague, 2015).…”
Section: Biopower: Bioresistancementioning
confidence: 60%
See 1 more Smart Citation
“…Yet their overwhelming sense of disempowerment often prompted a return to suspicious hermeneutics centred on resisting epistemic reductionism. While engendering a sense of agency, this also fed what I have described elsewhere as a recursive gridlock of biopolitical 'reproduction' and bio-epistemic 'resistance' (Béhague, 2015).…”
Section: Biopower: Bioresistancementioning
confidence: 60%
“…My fieldwork indicates that languages, values, and aesthetics linked to these two figures were being used and distributed in ways that brought history into a palpable and manipulable present. In the ethnographic and epidemiological studies of the Pelotas cohort, we found that young people were more likely to be framed (and to frame themselves) in behavioural terms – as agitated, inattentive, and with disordered conduct – if they were young men, reported lower family income, and if they identified as ‘black’ or of ‘mixed’ race ( Béhague, 2015 ). In contrast, a framing reminiscent of a psychoanalytic ‘storm-and-stress’ view of adolescence was more frequently used for and referenced by young women, and those who reported higher family incomes and identified as ‘white’.…”
Section: Biopower: Bioresistancementioning
confidence: 99%
“…In contrast, middle-class youth used antidepressants to temporarily facilitate the crucial work of refashioning a resilient internal self. These different uses served to reinforce long-standing views of the psychological inferiority of marginalised populations (Béhague 2015). These wide-ranging discourses surrounding antidepressant use demonstrate that, despite its globalisation, depression continues to be a localised 'polysemic symbol' (Barrett 1988: 375) DSM-IV, called the 'loss of sadness' (Frances 2013).…”
Section: Globalised Depressionmentioning
confidence: 93%
“…Prescription and use of psychotropic drugs-or their rejection-in mental health care, as Béhague (2015) has argued, do not result from a simple rational and instrumental adherence to a certain explanatory model of mental suffering (whether biopsychiatric, psychodynamic, or psychosocial). Such narratives and practices are immersed in "the broader moral, social, structural, and economic contingencies that drive (or circumvent) pharmaceuticalization" (Béhague 2015: 321).…”
Section: The Role Of Medication and Patient Groupsmentioning
confidence: 99%